The profile of patients attending the Groote Schuur Hospital Chronic Pain Management Clinic - Keenoo, Faadhila (Department of Anaesthesia and Perioperative Medicine, 2023)
Introduction Chronic pain affects 10- 25% of the population worldwide. However, studies of people with chronic pain have primarily been conducted in WEIRD (Western, Educated, Industrialised, Rich and Democratic) countries. There is a paucity of data from developing countries with the existing biased data being used to guide treatment of patients in developing countries. To address this knowledge gap, we have analysed the data of 623 patients attending the Chronic Pain Management Clinic (CPMC), at a tertiary facility in Cape Town, South Africa. The profile of the patients was compared to the global data. Methods A cross-sectional study of patients who attended the CPMC was conducted to describe their profile according to age, sociodemographic characteristics, health, gender and use of illicit drugs. Results The typical patient attending the CPMC was of middle age, female gender, of low educational level and less advantageous socio-economic status. They were also more likely to be on a disability grant and suffer from anxiety and depression. Conclusion The profile of the patients attending the CPMC was found to be similar to those from WEIRD countries. These results suggest that we can apply global data of people with chronic pain to patients attending this clinic.